2019
DOI: 10.4317/jced.55743
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intra-alveolar application of honey versus Chlorhexidine rinse on the incidence of Alveolar Osteitis following molar teeth extraction. A randomized clinical parallel trial

Abstract: Post-extraction application of honey versus Chlorhexidine rinse e871

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…Diversos estudios compararon la aplicación del enjuague de CHX con distintos grupos de control posterior a la extracción dental, y todos confirmaron que el enjuague de CHX, independiente de su concentración, ayuda a disminuir la incidencia el desarrollo de alveolitis seca (Sridhar et al, 2011;Osunde et al, 2017;Halabi et al, 2018;Abu-Mostafa et al, 2019;Karabit & Kattan, 2019;Divya et al, 2019). Dentro de estos estudios, encontramos el ensayo clínico aleatorizado doble ciego de Halabi et al (2018), quienes utilizaron enjuague de CHX al 0,12 % y agua esterilizada en grupos paralelos y estratificado por factores de riesgo (Tabaco, infección previa en el sitio quirúrgico y extracción traumática) obteniendo una incidencia de 2,69 % y 7,26 % respectivamente.…”
Section: Discussionunclassified
“…Diversos estudios compararon la aplicación del enjuague de CHX con distintos grupos de control posterior a la extracción dental, y todos confirmaron que el enjuague de CHX, independiente de su concentración, ayuda a disminuir la incidencia el desarrollo de alveolitis seca (Sridhar et al, 2011;Osunde et al, 2017;Halabi et al, 2018;Abu-Mostafa et al, 2019;Karabit & Kattan, 2019;Divya et al, 2019). Dentro de estos estudios, encontramos el ensayo clínico aleatorizado doble ciego de Halabi et al (2018), quienes utilizaron enjuague de CHX al 0,12 % y agua esterilizada en grupos paralelos y estratificado por factores de riesgo (Tabaco, infección previa en el sitio quirúrgico y extracción traumática) obteniendo una incidencia de 2,69 % y 7,26 % respectivamente.…”
Section: Discussionunclassified
“…Thus, further experimental studies are required to evaluate the efficacy of beeswax membrane in tissue regeneration. [17] RCT 100 patients Manuka honey used in the extraction socket following extraction found to be less efficient in the prevention of alveolar osteitis than chlorhexidine rinse. 3…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that rinsing with chlorhexidine solution before extraction there is 50% reduction of AO [73]. 0.12% chlorhexidine rinse on the day of extraction gave very promising results in prevention of AO [49].…”
Section: Chlorhexidinementioning
confidence: 99%
“…In one study, AO prevalence was 7.3% following single extractions and 3.4% following multiple extractions [32]. This difference could be a possibility due to the fact that patients with single extractions have less pain as compared to the patients with multiple extractions, whose teeth are damaged drastically Moreover, multiple extractions involving periodontal disease teeth may be less traumatic extraction gave very promising results in prevention of AO [49].…”
Section: Single Extraction Compared To Multiple Extractionsmentioning
confidence: 99%
See 1 more Smart Citation